Bibliotherapy: Reading OVID During COVID - Stip, Emmanuel; Östlundh, Linda; Abdel Aziz, Karim (Frontiers in Psychiatry, 2020)
An epidemic of an infectious disease such as COVID-19 is often a source of emotional distress, even among those who have not been directly exposed to the disease. The period following the acute phase of the coronavirus epidemic and the mitigation measures will likely be hardest for medical professionals in terms of psychological impact. Bibliotherapy is a systematic intervention regarding the use of carefully selected reading materials in order to help persons to cope with stress and personal problems. This therapy can be used easily during the pandemic. The review of evidence shows that this kind of intervention can be helpful in educational and clinical contexts. During the crisis, it can be an alternative to video and film entertainment and a transition from serious medical journal clubs to a softer medical humanities experience. In this article, we summarized the historical background of bibliotherapy. We also proposed a reading list from different times, and cultures relating to pandemic, quarantine, symptoms, confinement, and social impacts (e.g., Camus, Moravia, London, Le Clezio etc.). Bibliotherapy can be a way for doctors and healthcare workers fighting on the frontline of the pandemic to find psychological support and for debriefing. Bibliotherapy can help individuals that need support for emotional distress during the pandemic to verbalize their feelings and emotions and identify new ways of addressing problems.